2015
DOI: 10.1002/jcp.25201
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modulation in Periodontitis: Interaction of Adiponectin and JMJD3-IRF4 Axis in Macrophages

Abstract: Emerging evidence suggests an important role for epigenetic mechanisms in modulating signals during macrophage polarization and inflammation. JMJD3, a JmjC family histone demethylase necessary for M2 polarization is also required for effective induction of multiple M1 genes by lipopolysaccharide (LPS). However, the effects of JMJD3 to inflammation in the context of obesity remains unknown. To address this deficiency, we firstly examined the expression of JMJD3 in macrophage isolated from bone marrow and adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 26 publications
(42 reference statements)
0
32
0
2
Order By: Relevance
“…Consistent with peripheral inflammatory studies (Satoh et al ., ; Masuda et al ., ), our data suggested that microglial M1 and M2 phenotypes are also regulated by IRF5 and IRF4, respectively. Emerging data have demonstrated the IRF5/4 signaling was implicated in neurodegenerative (Zhu et al ., ; Song et al ., ) and infectious (Takaoka et al ., ; Balkhi et al ., ; Satoh et al ., ; Xuan et al ., ) diseases, and indicated that IRF5/4 are the key determinants for macrophage polarization upon inflammatory stimuli (Al Mamun & Liu, ). The present study found the expression of IRF5/4 in ischemic microglia is up‐regulated in a time‐dependent manner that is closely correlated with M1/2 phenotype, respectively, suggesting microglia share the same mechanism as that in peripheral monocytes to respond to self‐antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with peripheral inflammatory studies (Satoh et al ., ; Masuda et al ., ), our data suggested that microglial M1 and M2 phenotypes are also regulated by IRF5 and IRF4, respectively. Emerging data have demonstrated the IRF5/4 signaling was implicated in neurodegenerative (Zhu et al ., ; Song et al ., ) and infectious (Takaoka et al ., ; Balkhi et al ., ; Satoh et al ., ; Xuan et al ., ) diseases, and indicated that IRF5/4 are the key determinants for macrophage polarization upon inflammatory stimuli (Al Mamun & Liu, ). The present study found the expression of IRF5/4 in ischemic microglia is up‐regulated in a time‐dependent manner that is closely correlated with M1/2 phenotype, respectively, suggesting microglia share the same mechanism as that in peripheral monocytes to respond to self‐antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Dio2, PGC1α, and FOXC2) [23] is much higher than white adipose tissue (WAT) expression and in certain conditions, such as in caloric restriction (starvation or anorexia), WAT and MAT respond in opposite manners: while WAT decreases, MAT increases [26]. Brown adipose tissue (BAT), WAT and MAT also have been found to express very different levels of numerous adipokines [27]. In addition to the unique physiology of MAT, the close physical proximity of MAT and MM cells suggests unique, bidirectional signaling between MM cells and BM adipocytes unlike signaling between WAT and MM cells.…”
Section: Understanding the Bone Marrow Niche Cellular Componentsmentioning
confidence: 99%
“…48 In a research, it was found that adiponectin contributed to anti-inflammatory macrophage polarization by regulating JMJD3 expression, thus reducing macrophage infiltration. 49 Besides JMJD3, the absence of sirtuin-2 (SIRT2) promoted inflammatory responses by up-regulating the acetylation of NF-κB, thus reducing the M2-associated anti-inflammatory responses. 50 DNA methylation and transcription factor regulation are also involved in macrophage polarization.…”
Section: Epigenetics Regulates the Polarization State Of Macrophagesmentioning
confidence: 99%